2015
DOI: 10.4103/0976-9668.166097
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status and oral health behavior in hospitalized patients with chronic obstructive pulmonary disease

Abstract: Aim:We evaluated the periodontal health status and oral health behavior among hospitalized patients with chronic obstructive pulmonary disease (COPD) to assess the association of COPD with dental health.Materials and Methods:A group of 100 hospitalized patients with COPD and a group of 100 age, sex, and race-matched control patients were included in this study. Detailed case histories along with standardized measures of oral health including gingival index, plaque index (PI), and simplified oral hygiene index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 34 publications
(39 reference statements)
1
20
0
2
Order By: Relevance
“…In support of this, Bhavsar et al found patients in the COPD group, as a whole, had significantly reduced brushing frequency compared with a non-COPD group (independent of periodontal status) 95. Similarly, Liu et al found that a higher proportion of patients with frequent COPD exacerbations brushed their teeth less than once per day and had higher PI scores after adjusting for other confounding factors 104.…”
Section: Dental Habitsmentioning
confidence: 91%
See 1 more Smart Citation
“…In support of this, Bhavsar et al found patients in the COPD group, as a whole, had significantly reduced brushing frequency compared with a non-COPD group (independent of periodontal status) 95. Similarly, Liu et al found that a higher proportion of patients with frequent COPD exacerbations brushed their teeth less than once per day and had higher PI scores after adjusting for other confounding factors 104.…”
Section: Dental Habitsmentioning
confidence: 91%
“…Most studies investigating associations between COPD and periodontitis base the diagnosis of COPD on post- bronchodilator spirometry and GOLD staging 95,96,100,102,103,106. However, some authors used pre-bronchodilator spirometry,107 which could lead to an overestimation of the prevalence of COPD, others report lung function measurements but not whether pre- or post-bronchodilation,40,98 and one study failed to mention how COPD was confirmed 99.…”
Section: Potential Limitations Of These Studiesmentioning
confidence: 99%
“…And 171 records which are irrelevant or duplicate were excluded first after the titles and abstracts were screened, leaving 49 articles for a further full-text review. Eventually, 35 studies were excluded and 14 studies (Hayes et al, 1998 ; Scannapieco and Ho, 2001 ; Deo et al, 2009 ; Wang et al, 2009 ; Prasanna, 2011 ; Si et al, 2012 ; Ledić et al, 2013 ; Peter et al, 2013 ; Vadiraj et al, 2013 ; Yildirim et al, 2013 ; Öztekin et al, 2014 ; Bhavsar et al, 2015 ; Chung et al, 2016 ; Terashima et al, 2016 ) were eligible for inclusion in this analysis to perform the comparison of periodontal status between COPD and non-COPD subjects. The selection procedure is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The publication dates of the 14 included studies ranged from 1998 to 2016. Among the 14 studies, 12 (Hayes et al, 1998 ; Deo et al, 2009 ; Wang et al, 2009 ; Prasanna, 2011 ; Si et al, 2012 ; Ledić et al, 2013 ; Peter et al, 2013 ; Vadiraj et al, 2013 ; Yildirim et al, 2013 ; Öztekin et al, 2014 ; Bhavsar et al, 2015 ; Terashima et al, 2016 ) are case-control study (one of which is nested case-control study) and 2 are cross-sectional studies (Scannapieco and Ho, 2001 ; Chung et al, 2016 ). Totally 3348 COPD patients and 20612 non-COPD controls were studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation